Aerosolized ribavirin: the most expensive drug for pneumonia. Issue 4 (5th July 2016) - Chemaly, R.F.; Aitken, S.L.; Wolfe, C.R.; Jain, R.; Boeckh, M.J.
Abstract: Dramatic, overnight cost increases of important orphan and generic medications have recently come under public and government scrutiny. We highlight the case of aerosolized ribavirin, an important antiviral agent in hematopoietic stem cell transplantation which, because of substantial price increases, may now cost more than the transplant procedure itself.